2024
DOI: 10.3389/fcimb.2024.1345683
|View full text |Cite
|
Sign up to set email alerts
|

A review of neuro-ophthalmic sequelae following COVID-19 infection and vaccination

Jane Shi,
Helen V. Danesh-Meyer

Abstract: BackgroundIt has become increasingly clear that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can affect most organs in the human body, including the neurologic and ophthalmic systems. Vaccination campaigns have been developed at rapid pace around the world to protect the population from the fast-mutating virus. This review seeks to summarise current knowledge of the neuro-ophthalmic manifestations of both COVID-19 infection and vaccination.Evidence acquisitionElectronic searches for publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
0
0
0
Order By: Relevance
“…The COVID-19 pandemic has triggered a worldwide health emergency with far-reaching repercussions, surpassing the initial respiratory symptoms to include prolonged neurological complications, often termed ‘long COVID’ ( 1 ). Observational studies have potentially shown that COVID-19 can lead to disorders of optic nerve and visual pathways, including uveitis, optic neuritis, macular degeneration, and retinal vascular diseases ( 2 , 3 ). These conditions may manifest as a variety of symptoms, such as vision loss, visual field defects, reduced sensitivity to light and contrast, as well as alterations in color perception ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has triggered a worldwide health emergency with far-reaching repercussions, surpassing the initial respiratory symptoms to include prolonged neurological complications, often termed ‘long COVID’ ( 1 ). Observational studies have potentially shown that COVID-19 can lead to disorders of optic nerve and visual pathways, including uveitis, optic neuritis, macular degeneration, and retinal vascular diseases ( 2 , 3 ). These conditions may manifest as a variety of symptoms, such as vision loss, visual field defects, reduced sensitivity to light and contrast, as well as alterations in color perception ( 4 ).…”
Section: Introductionmentioning
confidence: 99%